2018
DOI: 10.1101/395681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput genotype based population structure analysis of selected buffalo breeds

Abstract: 13The water buffalo (Bubalus bubalis) has shown enormous milk production 14 potential in many Asian countries. India is considered as the home tract of some of the best 15 buffalo breeds. However, genetic structure of the Indian river buffalo is poorly understood. 16Hence, for selection and breeding strategies, there is a need to characterize the populations 17 and understand the genetic structure of various buffalo breeds. All rights reserved. No reuse allowed without permission.(which was not peer-reviewed) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…We observed the maximum LD score for chromosome 10 and largest LD block for chromosome Y. Similar results observed the LD decline at approximately 50 kb, with an average r 2 ≥ 0.2 in Chinese crossbred buffalo groups [Jianghan × Nili-Ravi × Mediterranean and Nili-Ravi × Murrah × local (Fuzhong or Xilin)] [ 67 ] and an r 2 value from 0.412 to 0.139 in Indian Nili-Ravi buffalo [ 68 ], which is much lower than that found in our study. However, comparing our findings directly with previous reports is difficult because of differences in the scale of sampling, given that the level of LD decreases with increasing sample size [ 69 ].…”
Section: Discussionsupporting
confidence: 82%
“…We observed the maximum LD score for chromosome 10 and largest LD block for chromosome Y. Similar results observed the LD decline at approximately 50 kb, with an average r 2 ≥ 0.2 in Chinese crossbred buffalo groups [Jianghan × Nili-Ravi × Mediterranean and Nili-Ravi × Murrah × local (Fuzhong or Xilin)] [ 67 ] and an r 2 value from 0.412 to 0.139 in Indian Nili-Ravi buffalo [ 68 ], which is much lower than that found in our study. However, comparing our findings directly with previous reports is difficult because of differences in the scale of sampling, given that the level of LD decreases with increasing sample size [ 69 ].…”
Section: Discussionsupporting
confidence: 82%
“…The results indicated that the selected SNPs may not be informative enough to reveal differences in Indian buffalo breeds. In a similar work, Thakor et al (2021) could differentiate phenotypically distinct breeds like Surti, Pandharpuri, and Jaffarabadi using SNPs in Axiom™ Buffalo Genotyping Array (90 K) but not others like Banni, Mehsana, Murrah and Niliravi. In a related development, Sudhakar et al (2021) studied false positive results of Deficiency of Uridine Monophosphate Synthase (DUMPS) in buffaloes which were tested using polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) tools developed for cattle and reported that using SNP detection genomic tools developed for a species requires genome sequencing for validation before using in a new species/population.…”
mentioning
confidence: 99%